DISPENSING ERRORS OBSERVED BY COMMUNITY PHARMACY DISPENSERS IN IBB - YEMEN - Al-worafi, Yaser Mohammed (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study was to determine the dispensing errors, its types, and causes in community pharmacies in Ibb, Yemen. Methods: A prospective study was conducted among community pharmacies in the Ibb, Yemen, over 4 months' period. Dispensing errors that were detected during the dispensing process were recorded by the pharmacy dispensers using a data collection form. Detecting and reporting of dispensing errors, types, and causes of dispensing errors were explained to the participated pharmacists before starting the study. The data were analyzed using the Statistical Package for the Social SciencesÂ® (IBM SPSS) version 21 for Windows. Results: A total of 35 (0.80%) dispensing errors were reported in this study. Wrong dosage form was the most common dispensing error type reported in this study followed by wrong quantity, wrong strength, and wrong drug. Factors most commonly reported as contributing to dispensing errors in this study were prescriptions poor handwriting, similar medications packaging, more than one patient at the same time, and similar drug names. Conclusion: This study explored the type and causes of dispensing errors at five community pharmacies in the Ibb city, Yemen. Dispensing errors can be prevented by educational interventions about dispensing error's and its potential causes. Effective collaboration and communication between community pharmacy dispensers and prescribers are an important key to minimize and prevent dispensing errors.